The scald crow - Daly, Grace (Creature Publishing, 2025)
Shot through with gallows humor and speaking in the voice of a trusted best friend, this self-deprecating horror novel explores medical trauma through Irish folklore, asking "Can a sick woman ever be trusted?" Brigid--that's the Irish Breej, not "Bridge-id," though it's not like she'd correct you--has had a rough go of it. Her mother abused her when she was little, her best friend (and secret crush) is too busy chasing some blonde to answer Brigid's calls, and she lost her job thanks to chronic pelvic pain with no identifiable cause. As a self-doubting, disabled adult, she's certain that everything that has happened to her is her fault. Now her mother has gone missing and Brigid's only option is to move back into her childhood home in the idyllic Midwestern town of St. Charles, Illinois. Soon the uncanny begins: A particular crow that once harassed her reappears, following her everywhere. A painting of Jesus keeps coming back, no matter how many times she throws it away. Frozen body parts show up in places rubber band balls and door stoppers ought to be. Every night the same nightmare repeats: her real mother is dead and decaying in the closet, and the identical mother who raised her is not her mother. But it's all in Brigid's head. It's all her fault. It must be. What other explanation could there be? After all, since when can a sick woman be trusted?